Teaching School Students through Distance Mode Some Reflections - Das, B.C. (JOURNAL OF INDIAN EDUCATION, 2010)
Teaching school students through chalk and talk approach has been in practice for long in India. Various strategies for achieving the present goal of school education were discussed and some are put into practice. In this paper it is argued that if teaching to school students, particularly Class IX students is offered through distance mode in the form of self-study material, they will prove to be more effective and economically viable. We think the case merits serious consideration as the issues raised remain significant.